An asymptotically stable sensorless speed controller for non‐salient permanent magnet synchronous motors. (16th October 2012) - Shah, D.; Espinosa–Pérez, G.; Ortega, R.; Hilairet, M.
SUMMARY A solution to the longstanding problem of sensorless control of an electrical machine is provided in this paper. That is, the construction of an asymptotically stable controller that regulates the mechanical speed of the motor, measuring only the electrical coordinates. The result is presented for a non‐salient permanent magnet synchronous motor perturbed by an unknown constant load torque. The proposed scheme is a fourth order nonlinear observer‐based controller that does not rely on—intrinsically nonrobust—operations like open‐loop integration of the systems dynamical model nor signal differentiation and can be easily implemented in real time. The controller is easy to commission, with the tuning gains directly determining the convergence rates of the position, speed, and load torque observers. Simulation and experimental results are presented. In particular, a comparison with a sensorless field‐oriented controller, recently proposed in the drives literature, is carried out. Copyright © 2012 John Wiley & Sons, Ltd.